Keterlibatan Amerika Serikat dalam Konflik Iran-Israel - Wijaya, Marko; Afif, Agung (Penerbit Minhaj Pustaka, 2025)
The purpose of this study is to determine involvement of the United States (US) in the Iran-Israel conflict. This conflict was triggered by the long-standing feud between Iran and Israel that has continued to heat up since the Iranian Revolution in 1979. The key event that became the study point of this research was the airstrike carried out by the United state (US) in 2020 that killed General Qassem Soleimani, the leader of Iran's Quds force, as well as Iran's counterattack that resulted in increased tension in the Middle East. Until 2025, the conflict continued with Iran launching drone and missile attacks on Israel in retaliation for attacks on Iranian diplomatic facilities. The United States (US) as Israel's main ally actively seeks to inhibit Iran's influence in the Middle East. The United States (US) provides military and diplomatic support to Israel to counter Iran's ambitions, including by supporting military operations in areas controlled by Iranian proxy militias such as in Syria and Iraq. This research uses Regional Hegemony theory and Rational Choice theory to analyze United States (US) interests in the Iran-Israel conflict in the region. Abstrak Tujuan dalam penelitian ini untuk menganalisis peran dan kepentingan amerika serikat (AS) dalam konflik Iran-Israel. Konflik ini dipicu oleh perseteruan berkepanjangan antara Iran dan Israel yang terus memanas sejak Revolusi Iran tahun 1979. Peristiwa penting yang menjadi titik kajian pada penelitian ini adalah serangan udara yang dilakukan oleh AS pada tahun 2020 yang menewaskan Jenderal Qassem Soleimani, pemimpin pasukan Quds Iran, serta serangan balasan Iran yang mengakibatkan ketegangan di Timur Tengah semakin meningkat. Hingga tahun 2025, konflik ini terus berlanjut dengan Iran melancarkan serangan drone dan rudal ke Israel sebagai balasan atas serangan yang dilakukan pada fasilitas diplomatik Iran. Amerika Serikat (AS) sebagai sekutu utama Israel secara aktif berupaya menghambat pengaruh Iran di Timur Tengah. Amerika Serikat (AS) memberikan dukungan militer dan diplomatik kepada Israel untuk melawan ambisi Iran, termasuk dengan cara mendukung operasi militer di wilayah-wilayah yang dikuasai oleh milisi proksi Iran seperti di Suriah dan Irak. Penelitian ini menggunakan teori Hegemoni Regional dan teori Rational Choice dalam menganalisis kepentingan Amerika Serikat (AS) dalam konflik Iran-Israel di kawasan ini.